Economic Efficiency of Pineapple Farming Using the Stochastic Frontier Approach - Adhiana, Adhiana; Ariani, Rita; Tanjung, Ade Firmansyah (Jurnal AGRISEP, 2024)
Central Aceh Regency is the province's largest pineapple producer. However, pineapple farming is facing the problem of low pineapple productivity and input use efficiency. The research aims to analyze the factors that influence the level of technical efficiency and the allocative and economic efficiency of pineapple farming in Pegasing District, Central Aceh Regency. The sampling process employs the stratified random sampling method. The total sample consisted of 62 respondents. The stochastic frontier is used. The research revealed that the production factor of land area, with a variable coefficient value of 0.0312, seeds with a variable coefficient value of seeds of 1.0152, and pesticides with a coefficient value of 5.6239, significantly influenced pineapple farming production in Pegasing District. Conversely, the labor factor, with a coefficient value of 0.0408, and fertilizer, with a coefficient value of 0.1198, had an insignificant effect. The use of inputs in pineapple farming has reached technical efficiency values, but there are ​still opportunities to increase optimally. However, neither allocatively nor economically have we achieved efficiency. The technical efficiency value for pineapple farmers was 0.80, the allocative efficiency value reached 0.427, and the economic efficiency was 0.351. Farmers, as actors in farming activities, need to pay attention to the use of the right combination of inputs; economic efficiency will be obtained from the use of production factors so that pineapple farmers' income will increase.